Pengaruh Status Sosial Ekonomi Keluarga dan Dukungan Sosial Terhadap Ketahanan Keluarga Penyintas Covid-19 - Fitriyatus Sholihah; Emy Susanti; Siti Mas'udah (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2023)
ENGLISHCovid-19 was not only a health problem, but also it has caused other problems in the economic, political, defense, and social and cultural sectors. The negative stigma of society towards patients, patients' families and people with a high risk of being exposed to Covid-19 was one of the impacts of this complex situation. This study aims to determine the simultaneous and partial effect of family socio-economic status and social support on the resilience of families of COVID-19 survivors. This is explanatory research with a quantitative approach. The method of data collection used a questionnaire. The analysis technique uses descriptive analysis, multiple linear regression analysis, F test and t test. Based on the results of the analysis, it shows that the socioeconomic status of the family and social support simultaneously affect the resilience of the family of Covid-19 survivors by 74.1%, while the remaining 25.9% is influenced by other variables not examined. Family socio-economic status and social support has a partial effect with a significant value of 0.000). Therefore, in the post-Covid-19 recovery effort, the provision of social support, especially to Covid-19 survivors and families with low socio-economic status, is urgently needed. It is for accelerating the recovery process helps Covid-19 survivors in realizing family resilience. INDONESIACovid-19 tidak hanya menjadi persoalan kesehatan, namun juga menimbulkan persoalan lain pada sektor ekonomi, politik, pertahanan, serta sosial dan budaya. Stigma negatif masyarakat pada pasien, keluarga pasien maupun orangorang dengan risiko tinggi terpapar Covid-19 menjadi salah satu dampaknya. Penelitian ini bertujuan untuk mengetahui pengaruh secara simultan dan parsial status sosial ekonomi keluarga dan dukungan sosial terhadap ketahanan keluarga penyintas Covid-19. Penelitian ini adalah explanatory research dengan pendekatan kuantitatif. Metode pengumpulan data menggunakan kuesioner. Teknik analisis menggunakan analisis regresi linier berganda, uji F dan uji t. Berdasarkan hasil analisis menunjukkan bahwa status sosial ekonomi keluarga dan dukungan sosial berpengaruh secara simultan terhadap ketahanan keluarga penyintas Covid-19 sebesar 74,1%, sedangkan sisanya sebesar 25,9% dipengaruhi oleh variabel lain yang tidak diteliti. Status sosial ekonomi keluarga dan dukungan sosial masing-masing berpengaruh secara parsial dengan nilai signifikan 0,000. Dalam upaya pemulihan pasca Covid-19, pemberian dukungan sosial khususnya kepada penyintas Covid-19 dan keluarga yang status sosial ekonominya rendah sangat dibutuhkan untuk mempercepat proses pemulihan penyintas Covid-19 dalam mewujudkan ketahanan keluarganya.